(untitled) (London Journal of Research In Humanities and Social Sciences, 2025)
Research on the vitality of Chetti Malay Creole, the heritage language of the Melaka Chetti community at Kampung Chetti, Malacca, have all reported a language shift. Since language shift often leads to language loss, this study seeks evidence of language loss and attrition among the younger generations, specifically among the fourth and fifth generations (G4/Gen Y and G5/Gen Z) Chettis. Using a language loss assessment (adapted from OGrady et al. 2009), the study found that Chetti lexicon is largely absent from the younger generations vocabulary and they struggle to construct short sentences in Chetti Malay, which indicate the lack of a working knowledge and use of their heritage language. Focus group interviews further reveal that many Chetti lexical items are unfamiliar to the younger generations since the language is spoken sporadically at festivals or among older generations. The findings place the vitality of Chetti Malay at Level 7 Shifting on the EGIDS while on the UNESCO Language Vitality and Endangerment framework Chetti Malay is definitely endangered. The study confirms that there is language shift, loss and attrition at Kampung Chetti. The study raises a critical question for further research on whether the lack of knowledge of Chetti vocabulary and the inability to use the language among the millennials and digital natives a case of attrition (total or partial forgetting of the vocabulary as a result of the language being rarely used) or incomplete acquisition (a language never acquired due to non-intergenerational transmission of Chetti Malay in their homes).